The association of body representation and nociceptive sensitivity measures with shoulder pain and disability prior to and twelve months after shoulder surgery - Bargon, Gabriella Maria (Curtin University, 2019)
Multidimensional factors have been identified for the development and persistence of shoulder pain. More recently alterations in the Central Nervous System (CNS) have been identified in musculoskeletal pain. This study aimed to determine the association between measures of body representation and nociceptive sensitivity, and shoulder pain and disability prior to and 12 months following rotator cuff surgery. Measures indicative of altered CNS processing were related to pain and disability prior to but not following surgery.